Hubungan karakteristik individu, personal higiene, dan kondisi fisik lingkungan dengan penyakit skabies pada warga binaan di Rumah Tahanan Negara Kelas I - Indah, Nur Fikrah Sri; Lubis, Rahayu (Talenta Publisher, 2024)
Scabies is an infectious disease caused by the parasite Sarcoptes scabiei var. hominis which is transmitted through interactions between humans with clinical symptoms of lesions characterized by itching, especially at night. In 2023 World Health Organization (WHO) estimates there are more than 200 million people worldwide at any one time. In Southeast Asia, scabies has a DALYs burden of 135.47 cases. The incidence of scabies in 2021 in North Sumatra Province was 811 people. At the class I State Detention Center in Medan, scabies is the highest infectious disease that is mostly suffered by 250 inmates. This study aims to determine the factors related to the incidence of scabies among inmates at the Medan Class I State Detention Center. This research method uses analytical methods with a cross-sectional design. The number of samples used in the research was 95 male inmates using a purposive sampling technique. Collecting research data through interviews using questionnaires and observation. The results of bivariate analysis showed that there was a significant relationship between knowledge (p<0.035), frequency of bathing (p< 0.025), cleanliness of hands and nails (p<0.001), clean clothing (p<0.001), bedding (p<0.001), and density (p<0.001) with the incidence of scabies in inmates in Medan class I state detention center. Inmates should maintain individual cleanliness, namely not borrowing and borrowing personal equipment, not washing clothes together with cellmates, drying bedding and other sleeping equipment at least once a week and continuing to keep the cell environment clean.